2001
DOI: 10.1097/00005650-200101000-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Work Limitations Questionnaire

Abstract: With 25 items, 4 dimensions (limitations handling time, physical, mental-interpersonal, and output demands), and a 2-week reporting period, the Work Limitations Questionnaire demonstrated high reliability and validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
576
2
31

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 835 publications
(631 citation statements)
references
References 9 publications
1
576
2
31
Order By: Relevance
“…Survivors of adolescent cancer in our sample were not less likely to be employed or work part-time than their healthy counterparts; however, survivors of adolescent cancer did report reduced work quality and quantity as compared to healthy controls (Lerner et al, 2001).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Survivors of adolescent cancer in our sample were not less likely to be employed or work part-time than their healthy counterparts; however, survivors of adolescent cancer did report reduced work quality and quantity as compared to healthy controls (Lerner et al, 2001).…”
Section: Discussioncontrasting
confidence: 55%
“…The Work Limitations Questionnaire (WLQ) (Lerner et al, 2001) is a 25-item self-report measure of work functioning. The WLQ has shown reliability and validity for use among several different jobs and chronic health condition groups including those with cancer (Gordon et al, 2011).…”
Section: Perceived Cognitive Function Patients Assessment Of Own Funmentioning
confidence: 99%
“…The validated Work Limitations Questionnaire (WLQ) [17,18] has been used in studies of brain tumors, depression, arthritis and migraine [19][20][21][22]. For example, Feuerstein et al (2007) found that brain tumor survivors reported more time lost from work and lower work productivity than a comparison group [19].…”
mentioning
confidence: 99%
“…Presenteeism was measured by the Work Limitation Questionnaire (WLQ: Lerner, Amick, Rogers, Malspeis, & Bungay, 2001), a self-report with 25 items. It measures employee's ability to perform four specific set of job demands including Time Management (TMM: five items, e.g., difficulty working required hours), Physical Demand (PHD: six items, e.g., ability to walk to different work locations), Mental and Interpersonal Demands (MID: nine items, e.g., difficult doing work carefully) and Output Demands (OPD: five items, e.g., difficulty handling the workload).…”
Section: Presenteeismmentioning
confidence: 99%